Investigating decision-making under risk in pathological gambling using a virtual slot machine: a pilot eye-tracking study : behavioral addictions and gambling - Baumann, Gloria; Fischer, Ronald; Reinhard, Iris; Hoffmann, Sabine; Kiefer, Falk; Leménager, Tagrid; Bach, Patrick (European addiction research, 2025)
Introduction: Pathological gambling (PG) is characterized by altered decision-making. Even though studies have investigated decision-making in patients with PG, the effects of win-contingent stimuli thereon are not well understood yet. Methods: Thus, we conducted a study in patients with PG (n = 10) and healthy individuals (n = 14), who performed two versions of a slot machine gambling task with and without win-contingent cues, while decision-making and gaze fixations were assessed using high-resolution eye-tracking. Results: Patients with PG showed higher rates of high-risk decisions, lower rates of rational choices and showed less visual attention to probability information, but increased visual attention toward gambling cues, compared to healthy individuals. In the presence of win-contingent gambling cues, participants needed significantly more time to decide between high-risk versus low-risk gambles and spent significantly less time watching the probability information. Conclusion: Findings highlight the relevance of gambling-associated cues in PG. Targeting altered cue-reactivity could contribute to normalizing risky decision-making in patients with PG.